Preliminary Investigations on Salmonella spp. Incidence in Meat Chicken Farms in Italy, Germany, Lithuania and the Netherlands - Pieskus, Juozas; Franciosini, Maria Pia; Proietti, Patrizia Casagrande; Reich, Felix; Kazeniauskas, Edvardas; Butrimaite-Ambrozeviciene, Ceslova; Mauricas, Mykolas; Bolder, Nico (International Journal of Poultry Science, 2008)
The broiler chickens, especially if intensively reared, can be considered as an important reservoir of Salmonella infections in humans. Many consumers assume that broiler chickens, grown under conventional commercial conditions, have higher infection levels of Salmonella than free-range organic chickens. The subject of this study was firstly to assess the incidence of Salmonella spp. In conventional chicken farms, located in different areas of Italy, Germany, Lithuania and in the Netherlands. In addition organic farms were investigated both in Italy and the Netherlands. The typification of Salmonella was also effected in attempt to value the distribution of the organism on the basis of the different geographical areas. The incidence of Salmonella in “conventional” broiler farms was 29% in Lithuania, 20% in Italy and 11% in The Netherlands, while in Germany Salmonella was not detected. Salmonella was isolated from organic broiler flocks in Italy (18, 1%) and in The Netherlands (3, 7%). Our results indicated that Salmonella Enteritidis and Salmonella Typhimurium dominated in Lithuanian broiler flocks while Salmonella Infantis and Salmonella Java were predominant in the Netherlands. Salmonella hadar and Salmonella heidelberg seemed to be prevalent in Italy.